What Is the Important Point Related to Follow-Up Sonographic Evaluation for the Developmental Dysplasia of the Hip? - Donma, M. M.; Dogru, M.; Demirkol, M.; Ozcaglayan, O.; Topcu, B.; Ozcaglayan, T. I. K.; Gonen, K. A.; Nalbantoglu, B.; Nalbantoglu, A.; Dogru, R.; Ulucan, H.; Karakoyun, O.; Erol, M. F.; Guzelant, A. Y.; Donma, O. (Journal of Child Science, 2017)
Developmental dysplasia of the hip (DDH) is an important cause of childhood disability. Subluxation or dislocation can be diagnosed through pediatric physical examination; nevertheless, the ultrasonographic examination is necessary in diagnosing certain borderline cases. It has been evaluated routine sonographic examination of 2,444 hips of 1,222 babies to determine differences in both, developmental dysplasia and types of hips, and evaluated their development on the 3-month follow-up. Evaluating the pathologic “α” angles under 59, there was no statistically significant differences between girls and boys in both right (55.57 ± 3.73) (56.20 ± 4.01), (p = 0.480), and left (55.79 ± 3.96) (57.00 ± 3.84), (p = 0.160) hips on the 45th day of life. Routine sonographic examinations on the 45th day of life revealed that 51 of (66.2%) 77 type 2a right hips were girls and 26 (33.8%) were boys. The number of the right hips that develop into type 1 was 38 (74.5%) for girls and 26 (100%) for boys on the 90th day of life (p = 0.005). A total of 87 type 2a left hips included 64 girls (73.6%) and 23 boys (26.4%). In the 90th day control, 49 right hip of girls (76.6%) and 21 right hip of boys (91.3%) developed into type 1 (p = 0.126). In the assessment of both left and right hips, girls showed a significantly higher frequency in latency and boys showed significantly higher development in the control sonography. A total of 31 girls (2.5%) and 11 boys (0.9%) accounted for a total of 42 (3.4%) cases who showed bilateral type 2a hips in 1,222 infants. On the 90th day control, 26 girls (83.9%) and all 11 boys (100%) developed into type 1 (p = 0.156). The study emphasizes the importance of the sonographic examination on the 90th day of life. Results of the investigation include the data of sonographic screening of DDH on the 45th day, and also stress the importance of the 90th-day control sonography after a close follow-up with physical examination between 45th and 90th days of life.
Keywords: developmental dysplasia of the hip; sonography; follow-up examination